2013
DOI: 10.2147/ccid.s41578
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal skin darkening in Chinese women: the Shanghaiese experience of daily sun protection

Abstract: The facial skin tone of two groups of Chinese women from Shanghai was compared using standard colorimetric space techniques during a 6-month interval between January and July 2011. During the study period, one group of women (n = 40) applied a potent sun-protective cosmetic product daily, while the other group (n = 40) did not use any sun protection. The results, based on images taken using a standardized digital camera coupled to a spectroradiometer, showed that sun protection largely mitigated changes in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 15 publications
4
46
0
Order By: Relevance
“…Others have demonstrated that the use of particular cosmetic products or moisturizers during the winter season was able to ameliorate the loss of surface moisture during the cold, dry season . In addition, the use of sun protection products has also been shown to protect against the seasonal darkening observed during summer . It would be worth investigating if the same benefits could also be achieved in the different ethnicities included in this study.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Others have demonstrated that the use of particular cosmetic products or moisturizers during the winter season was able to ameliorate the loss of surface moisture during the cold, dry season . In addition, the use of sun protection products has also been shown to protect against the seasonal darkening observed during summer . It would be worth investigating if the same benefits could also be achieved in the different ethnicities included in this study.…”
Section: Discussionmentioning
confidence: 89%
“…Asian, Caucasian, etc.) (2,7,19), reflecting a common response to changes in UV exposure regardless of ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sun exposures are governed by necessities (residential, occupational factors) and geographical or weather conditions such as latitude, altitude, season, working conditions (indoor vs. outdoor), fluctuations in the weather annual sunshine… Combined, these strongly modulate the flux of ultraviolet (UV) rays and largely extend the palette of individual cases and their consequent variable impact upon skin structure, functions and perceived age (i.e. older or younger than real/chronological age..) . Another work compared the facial signs of French ‘sun‐seekers’ to ‘sun‐phobic’ women living in a very sunny region of France, illustrating how these slight changes (pigmented spots or global skin darkening, wrinkles..) are additional to and how they likely speed up the skin changes that progressively appear along the natural, chronological ageing .…”
Section: Introductionmentioning
confidence: 99%
“…Combined, these strongly modulate the flux of ultraviolet (UV) rays and largely extend the palette of individual cases and their consequent variable impact upon skin structure, functions and perceived age (i.e. older or younger than real/chronological age..) [12][13][14][15]. Another work [14] compared the facial signs of French 'sun-seekers' to 'sun-phobic' women living in a very sunny region of France, illustrating how these slight changes (pigmented spots or global skin darkening, wrinkles..) are additional to and how they likely speed up the skin changes that progressively appear along the natural, chronological ageing [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…These two populations show very similar skin color characteristics, but differ in their living environment. Many reports on the skin color of these two Asian populations exist . However, direct data are difficult to compare by differences in study protocols and conditions.…”
Section: Introductionmentioning
confidence: 99%